2022
DOI: 10.3389/fpls.2022.816425
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Quinoa Seed Quality: Identification of Novel Candidate Genetic Markers for Increased Protein Content

Abstract: Quinoa (Chenopodium quinoa Willd.) is a crop that has great potential for increased cultivation in diverse climate regions. The seed protein quality obtained from this crop is high concerning the requirements to meet human nutritional needs, but the seed protein content is relatively low if compared to crops such as grain legumes. Increased seed protein content is desirable for increasing the economic viability of this crop in order for it to be used as a protein crop. In this study, we characterized three gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…Among these traits, crude protein, total amino acid content, and ash content had strong positive correlations with one another, while crude protein had a moderate positive correlation with crude fat content. In a study of Pasankalla, Titicaca, and Regalona, Grimberg et al. (2022) found Pasankalla to have the highest protein and oil content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these traits, crude protein, total amino acid content, and ash content had strong positive correlations with one another, while crude protein had a moderate positive correlation with crude fat content. In a study of Pasankalla, Titicaca, and Regalona, Grimberg et al. (2022) found Pasankalla to have the highest protein and oil content.…”
Section: Resultsmentioning
confidence: 99%
“…Storage proteins increase significantly in quinoa during maturation, in addition to oil accumulation, which provides evidence of a possible tradeoff between maturation and seed composition ( Shen et al., 2022 ). For instance, Grimberg et al. (2022) found Pasankalla matured 13 days after Titicaca and Regalona under controlled conditions (12-hour days) and had significantly higher protein and oil content.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 21 of the 41 genes were annotated with functions and GO terms, with 40% of them directly related to reproduction or seed development (Table S6 ). We used publicly available shotgun proteomics (Poza‐Viejo et al ., 2023 ) and transcriptomics (Grimberg et al ., 2022 ) data from quinoa seeds to assess the expression of the 41 candidate genes. Our results showed that 27 of the 41 candidates could be detected in the proteome and 39 of the 41 candidate genes could be detected in the transcriptome.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested high-precision candidate markers for nutritional traits in quinoa (Grimberg et al, 2022). Previous studies also showed the value of Chenopodium leaves as a vegetable supplement; such studies might be considered in C. album for future studies (Bhargava et al, 2019).…”
Section: Discussionmentioning
confidence: 96%